1997
DOI: 10.1021/jm9607212
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor Agonists:  Synthesis, Protolytic Properties, and Pharmacology of 3-Isothiazolol Bioisosteres of Glutamic Acid

Abstract: A number of 3-isothiazolol bioisosteres of glutamic acid (1) and analogs of the AMPA receptor agonist, (RS)-2-amino-3-(3-hydroxy-5-methylisoxazol-4-yl)propionic acid (AMPA, 2a), including (RS)-2-amino-3-(3-hydroxy-5-methylisothiazol-4-yl)propionic acid (thio-AMPA, 2b), were synthesized. Comparative in vitro pharmacological studies on this series of 3-isothiazolol and the corresponding 3-isoxazolol amino acids were performed using a series of receptor binding assays (IC50 values) and the electrophysiological ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 43 publications
0
58
0
1
Order By: Relevance
“…4D, w1) is found near Gly-653 (equivalent to Gly-675 in GluR-D) only in the AMPA complex. This water molecule plays a key role in agonist binding, forming hydrogen bonds with the oxygen atom at the 3-position of the isoxazole ring, shown to be unprotonated (21), to the ␣-carboxylate of AMPA, and to the main chain NH group of Thr-655 (Thr-677 in GluR-D). The distance between the ␣-carbon of Gly-653 to the oxygen atom of w1 is 3.3 Å, whereas with the glycine-to-alanine mutation, the distance between the methyl carbon in the alanine side chain and w1 would be only about 2.0 Å (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4D, w1) is found near Gly-653 (equivalent to Gly-675 in GluR-D) only in the AMPA complex. This water molecule plays a key role in agonist binding, forming hydrogen bonds with the oxygen atom at the 3-position of the isoxazole ring, shown to be unprotonated (21), to the ␣-carboxylate of AMPA, and to the main chain NH group of Thr-655 (Thr-677 in GluR-D). The distance between the ␣-carbon of Gly-653 to the oxygen atom of w1 is 3.3 Å, whereas with the glycine-to-alanine mutation, the distance between the methyl carbon in the alanine side chain and w1 would be only about 2.0 Å (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For stimulation of glutamate receptors (NMDA, AMPA, Kainate and metabotropic receptor) four agonists were used, respectively: trans-1-Aminocyclobutan-1,3-dicarboxylic acid (ACBD [13], (S)-(-)-α-Amino-5-fluoro-3,4-dihydro-2,4-dioxo-1(2H)-pyrimmidinepropanoic acid (S-Fluorowillardiine [14]- [16], (RS)-2-Amino-3-(3-hydroxy-5-tert-butyliosxazol-4-yl)propanoic acid (ATPA; [17]- [20] and (±)-1-Aminocyclopentane-trans-1,3-dicarboxylic acid (t-ACPD; [21]- [23]. All agonists were tested in pilot experiments in order to detect a concentration leading to strong increases of population spike amplitude in the presence of single stimuli (SS) and theta burst stimulation (TBS).…”
Section: Hippocampal Slice Preparation In Vitromentioning
confidence: 99%
“…5). Replacement of the 3-isoxazolol acidic moiety of AMPA with the corresponding 3-isothiazolol provided thio-AMPA 48 (Fig. 4).…”
Section: Ampa Analogsmentioning
confidence: 99%
“…Although the pKa value of the distal acidic group of AMPA is almost two units lower than that of thio-AMPA, comparable selectivity and activity at AMPA receptors were observed for AMPA and thio-AMPA. 48 Resolution of thio-AMPA and pharmacological characterization of the enantiomers revealed that the affinity and agonist activity resides exclusively in the S-enantiomer 49 ( Table 1). As in the case of (R)-AMPA, no antagonist effects were observed for (R)-thio-AMPA on the rat cortical wedge.…”
Section: Ampa Analogsmentioning
confidence: 99%